Thematical feast: from tradition to modernity - Gastal, Susana de Araujo; Machiavelli, Mariana Schwaab; Guterres, Liliane Stanisçuaski (Revista Turismo em Análise, 2013)
To celebrate is a personal and collective form of expression, present in different cultures, making the feast a major event for individuals and communities. Nowadays the popular feasts are very common in southern Brazil, but often criticized for its lack of authenticity in its relation to local cultures. This article proposes to reconstruct the historical background of the feasts in modernity from the great world exhibitions of European second half of the nineteenth century to carnival aesthetic influence in the second half of the twentieth century. These events influenced the organization of local feast in Brazil, including the popular one, trying to adapt them to new modern demands for leisure and entertainment. This article is mostly based on it to propose the term "thematical feast" to design these events in this new logic.